Bridging the Equity Gap: The Efficacy of Assistive Mobile Technologies for Special Needs Students in Low-Resource Settings - Aiman Fariq; Jemima Reid; David Mayers (Journal Emerging Technologies in Education, 2026)
Background: Service learning has gained significant attention in higher education as an effective pedagogical approach that combines academic learning with community service. By engaging students in real-world problem-solving, service learning fosters both academic achievement and civic responsibility. However, its integration into higher education curricula remains inconsistent, and its impact on student learning and development requires further exploration. Purpose: This study aims to examine the effectiveness of integrating service learning into higher education curricula and its impact on students' academic and personal development. Specifically, it explores how service learning enhances critical thinking, social responsibility, and community engagement among university students. Method: A mixed-methods approach was used, combining quantitative surveys and qualitative interviews. Data were collected from 150 students enrolled in service learning courses across various disciplines. Pre- and post-course surveys assessed academic performance, while interviews provided insights into students' personal reflections on their experiences. Results: The findings indicate that students who participated in service learning courses showed significant improvements in critical thinking skills, social responsibility, and their sense of community involvement. These students also reported higher levels of academic engagement and satisfaction compared to those in traditional courses. Conclusion: Integrating service learning into higher education curricula effectively enhances students' academic, personal, and social development. The study highlights the importance of incorporating experiential learning opportunities that bridge classroom knowledge with real-world applications.